Characterization and Antibiotic Sensitivity Profile of Bacteria Isolated from Patients with Respiratory Tract Infections in Bangladesh - Promite, Shukla; Saha, Sajal K; Ahsan, Sunjukta; Akhter, Marufa Zerin (Dhaka University Journal of Pharmaceutical Sciences, 2018)
The study was aimed to characterize bacterial isolates from respiratory tract infections (RTI) and investigate their antibiotic sensitivity profile. Selective media and biochemical tests were used to characterize 40 bacterial isolates. Antibiotic sensitivity testing was conducted using Kirby-Bauer disc diffusion method. About 42.5% (17) RTI patients were infected by Klebsiella pneumoniae, 30% (12) by Escherichia coli and 27.5% (11) by Pseudomonas aeruginosa with no significant gender variation (p-value <0.578). Overall, 47% (out of 20) antibiotics were sensitive, whereas 48% were resistant. Surprisingly, 18% P. aeruginosa and 20% K. pneumoniae were carbapenem-resistant and 4 out of 7 cephalosporin antibiotics were highly resistant irrespective of pathogens. E. coli showed better sensitivity to nitrofurantoin (78%) and levofloxacin (89%), while K. pneumoniae was insensitive to cotrimoxazole (88%), gentamycin (77%) and piperacillin/tazobactam (66%). On the other hand, P. aeruginosa did not respond to P. aeruginosa to nalidixic acid (60%) and ciprofloxacin (60%). This study concludes that nitrofurantoin, levofloxacin, cotrimoxazole, gentamycin and piperacillin/tazobactam antibiotics could be better alternative in treating bacterial RTIs. Dhaka Univ. J. Pharm. Sci. 16(2): 235-244, 2017 (December)